People with severe and profound intellectual disability: Nurse carer experiences in a South African setting. Issue 1 (2nd January 2018) - Manaka, Dikeledi; van der Wath, Annatjie; Moagi, Miriam
Abstract : We explored nurse carer experiences with people with severe and profound intellectual disability in a care and rehabilitation centre in South Africa. Informants were a convenience sample of 10 nurses (females = 7; males = 3; mean years of service = 7.8, SD = 4.8 years). They completed an unstructured interview on their care provision experiences. The data were thematically analysed using Tesch's method of open coding. Findings resulted in the following three themes to characterise the nurse carer experiences: compassion, person-centred care, and importance of parent involvement. Compassionate and person-centred care is fundamental to the establishment of a therapeutic relationship between nurse carers and people with severe and profound intellectual disability.